The foreigner [videorecording (DVD)] - Campbell, Martin; Cheng, Long, 1954-; Brosnan, Pierce; Leung, Katie, 1987-; Leather, Stephen (Universal Pictures Home Entertainment, 2017)
After his only daughter gets killed in a terrorist attack, a former Vietnam War special forces operator begins the search for the terrorists' identities to get his revenge.